1999
DOI: 10.1681/asn.v102392
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Dry Weight in Hemodialysis

Abstract: Abstract. Fluid balance is an integral component of hemodialysis treatments to prevent under- or overhydration, both of which have been demonstrated to have significant effects on intradialytic morbidity and long-term cardiovascular complications. Fluid removal is usually achieved by ultrafiltration to achieve a clinically derived value for “dry weight.” Unfortunately, there is no standard measure of dry weight and as a consequence it is difficult to ascertain adequacy of fluid removal for an individual patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(26 citation statements)
references
References 73 publications
0
26
0
Order By: Relevance
“…However, it has been reported that the BIS based DW prediction does not match the DWCW in some hemodialysis patients. An overestimated DWBIS (associated with a negative DWCP-BIS) is higher than the DWCP; in this situation, edema, chest discomfort, dyspnea, and uncontrolled hypertension may develop [21][22][23]. An underestimated DWBIS (associated with a positive DWCP-BIS) is lower than the DWCP; in this situation, hypotension, cramping, dizziness, and altered consciousness may develop [24,25].…”
Section: Discussionmentioning
confidence: 96%
“…However, it has been reported that the BIS based DW prediction does not match the DWCW in some hemodialysis patients. An overestimated DWBIS (associated with a negative DWCP-BIS) is higher than the DWCP; in this situation, edema, chest discomfort, dyspnea, and uncontrolled hypertension may develop [21][22][23]. An underestimated DWBIS (associated with a positive DWCP-BIS) is lower than the DWCP; in this situation, hypotension, cramping, dizziness, and altered consciousness may develop [24,25].…”
Section: Discussionmentioning
confidence: 96%
“…The “dry weight,” which is the most commonly used method in HD to assess solute removal, is dependent on knowledge of the body compartment capacities and the amounts of water and sodium in each compartment. 11) Unfortunately, this method is imprecise and cannot easily identify changes in nutritional status and lean body mass. As a consequence, acute and chronic over- or under-hydration are common among dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…This weight should be similar to what a person with normal kidney function would weigh after urinating. There is no standard measure of dry weight, so it is difficult to ascertain the adequacy of fluid removal for individual patients [8]. Several different techniques, including inferior diameter, natriuretic peptide, and bioimpedance, were used to derive a more standard method of assessing dry weight [9][10][11][12]; however, no single method has 2 of 14 emerged as a gold standard, so nephrologists need to frequently adjust the patient's dry weight on the basis of interdialytic weight gain and intradialytic hemodynamic changes [13].…”
Section: Introductionmentioning
confidence: 99%